Effect of needle cone angle and air flow rate on electrostatic discharge characteristics of a corona-needle ionizer - Panich Intra (2018)
In this study, the corona-needle ionizer was designed, constructed, and characterized. Experimental characterizations of the electrostatic discharge in terms of current-voltage relationships of the corona ionizer, including the effects of discharge electrode cone angle and air flow rate were presented. It was found that the charging current and ion concentration in the charging zone increased monotonically with corona voltage. Conversely, discharge currents decreased with increasing angle of the needle cone. The negative corona was found to have higher current than the positive corona. At higher air flow rates, the ion current and concentration were found to be relatively high for the same corona voltage. The effect of air flow rate was more pronounced than the corona voltage. It was also shown that the ion penetration through the ionizer decreased with increasing corona voltage, and increased with increasing air flow rate. The highest ion penetration through the ionizer of the 10° needle cone angle was found to be about 93.7 and 7.7% for positive and negative coronas, respectively. The highest ion penetration for the needle cone angle of 20° was found to be 96.6 and 6.1% for positive and negative coronas, respectively. © 2010 Elsevier B.V.